Transcendentalism and Tischner’s work - Wesołowska, Agnieszka (Folia Philosophica, 2012)
Review of Anna Borowicz's book: Transcendentalism in Józef Tischner's Philosophy. Gdańsk: Gdańsk University Press, 2010.